Firm-bank relationships: A cross-country comparison - Kamelia Kosekova; Angela Maddaloni; Melina Papoutsi; Fabiano Schivardi (European Central Bank (ECB), 2023)
We document the structure of firm-bank relationships across eleven euro area coun- tries and present new stylised facts using data from the Eurosystem credit registry - AnaCredit. We look at the number of banking relationships, reliance on the main bank, credit instruments, loan maturity, and interest rates. Firms in Southern Europe borrow from more banks and obtain a lower share of credit from the main bank than those in Northern Europe. They also tend to borrow more on short term, more expensive instruments and to obtain loans with shorter maturity. This is consistent with the hypothesis that firms in Southern Europe rely less on relationship banking and obtain credit less conducive to firm growth, in line with their smaller average size. Relationship lending does not translate in lower rates, possibly because banks appropriate part of the surplus generated by relationship lending through higher rates.
Keywords: G21; G3; G32; 330; AnaCredit; Firm-bank relationship; Corporate financing; Bank Credit